Surgical Masks Affect the Peripheral Oxygen Saturation and Respiratory Rate of Anesthesiologists - Yang, Shaozhong; Fang, Chuanyu; Liu, Xin; Liu, Yu; Huang, Shanshan; Wang, Rui; Qi, Feng (Frontiers in Medicine, 2022)
Background Surgical masks (SMs) protect medical staff and reduce surgical site infections. Extended SM use may reduce oxygen concentrations in circulation, causing hypoxia, headache, and fatigue. However, no research has examined the effects of wearing SMs on oxygenation and physical discomfort of anesthesiologists. Methods An electronic questionnaire was established and administered through WeChat, and a cross-sectional survey was conducted to determine SM use duration and related discomfort of operating room medical staff. Then, operating room anesthesiologists were enrolled in a single-arm study. Peripheral blood oxygen saturation (SpO2), heart rate, and respiratory rate were determined at different times before and after SM use. Shortness of breath, dizziness, and headache were subjectively assessed based on the visual analog scale (VAS) scores. Results In total, 485 operating room medical staff completed the electronic questionnaire; 70.5% of them did not change SMs until after work, and 63.9% wore SMs continuously for more than 4 h. The proportion of anesthesiologists was the highest. After wearing masks for 4 h, the shortness of breath, fatigue, and dizziness/headache rates were 42.1, 34.6, and 30.9%, respectively. Compared with other medical staff, the proportion of subjective discomfort of anesthesiologists increased significantly with prolonged SM use from 1 to 4 h. Thirty-five anesthesiologists completed the study. There was no difference in anesthesiologist SpO2, heart rate, or respiratory rate within 2 h of wearing SMs. After more than 2 h, the variation appears to be statistically rather than clinically significant—SpO2 decreased (98.0 [1.0] vs. 97.0 [1.0], p < 0.05), respiratory rate increased (16.0 [3.0] vs. 17.0 [2.0], p < 0.01), and heart rate remained unchanged. As mask use duration increased, the VAS scores of shortness of breath, dizziness, and headache gradually increased. Conclusion In healthy anesthesiologists, wearing SMs for more than 2 h can significantly decrease SpO2 and increase respiratory rates without affecting heart rates.